Horizontal and Vertical Differentiation: Approaching Endogenous Measurement in Intra-industry Trade - Sourish Dutta (Cambridge Open Engage, 2023)
Studying intra-industry trade involves theoretical explanations and empirical methods to measure the phenomenon. Indicators have been developed to measure the intensity of intra-industry trade, leading to theoretical models explaining its determinants. It is essential to distinguish between horizontal and vertical differentiation in empirical analyses. The determinants and consequences of intra-industry trade depend on whether the traded products differ in quality. A method for distinguishing between vertical and horizontal differentiation involves comparing exports' unit value to imports for each industry's intra-industry trade. This approach has limitations, leading to the need for an alternative method.
Keywords: F10; F11; F12; F14; 330; Intra-industry trade; Vertical intra-industry trade; Horizontal intra-industry trade; Value Added